2023
DOI: 10.3390/nu15030778
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Eating and Changes in High-Sugar Food and Drink Consumption Linked to Psychological Distress and Worries: A Cohort Study from Norway

Abstract: Psychological distress is linked to unhealthy eating behaviors such as emotional eating and consumption of high-sugar food and drinks. Cross-sectional studies from early in the COVID-19 pandemic showed a high occurrence of worries and psychological distress, and this was associated with emotional eating. Few larger studies have examined how this coping pattern develops over time. This cohort study with 24,968 participants assessed changes over time in emotional eating, consumption of sugary foods as an example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This suggests that factors other than EE may contribute to obesity. In our previous study on the same cohort, we established that EE was reduced over time during different phases of the pandemic [50]. We argued that one possible explanation could be related to the state of chronic stress.…”
Section: Discussionmentioning
confidence: 76%
“…This suggests that factors other than EE may contribute to obesity. In our previous study on the same cohort, we established that EE was reduced over time during different phases of the pandemic [50]. We argued that one possible explanation could be related to the state of chronic stress.…”
Section: Discussionmentioning
confidence: 76%
“…Regarding body fat, there were no significant changes in fat mass or percentage of fat, although athletes increased their total body mass. In non-athletes, Javadi Arjmand et al conducted a cohort study with 24,968 participants and found that high psychological distress was strongly associated with higher levels of emotional eating and high-sugar food intake [ 53 ]. In fact, the consumption of high caloric foods, due to impulse or anxiety, as well as lower levels of healthy eating habits were found, mainly at the start of the pandemic, which can maybe explain the changes in total body mass.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Psychological distress (PD; negative stress) is a general term that refers to nonspecific symptoms of depression, anxiety, and stress. 3 As one of the most vital risk factors for developing severe mental disorders, PD causes a significant rise in anxiety and depression. A substantial amount of research has focused on the effects of PD on health, particularly after the outbreak of coronavirus disease 2019 (COVID-19).…”
mentioning
confidence: 99%
“…Mental disorders are the leading contributors to the global health‐related burden, as they substantially affect daily functioning and quality of life, increase health care costs, and shorten life expectancy 1,2 . Psychological distress (PD; negative stress) is a general term that refers to nonspecific symptoms of depression, anxiety, and stress 3 . As one of the most vital risk factors for developing severe mental disorders, PD causes a significant rise in anxiety and depression.…”
mentioning
confidence: 99%